Phytochemical Screening and Antioxidant Activity Test of Puring Leaf Extract (Codiaeum variegatum (L.) Rumph. ex A. Juss.) in Various Solvents Using the DPPH (2,2-diphenyl-1-picrylhydrazil) Method - Putu Sanitha Jayanti; Dewi Puspita Apsari; I Putu Gede Adi Purwa Hita; I Gusti Ngurah Agung Dharma Randika Putra (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2026)
Background: Free radicals are molecules or compounds that exist independently and possess one or more unpaired electrons. Free radicals may infiltrate the body and damage healthy cells, leading to degenerative disorders. The detrimental effects they induce can be mitigated using antioxidant substances. Antioxidants are substances that inhibit the oxidation of molecules and can neutralize free radicals, even in minimal quantities. The croton leaf (Codiaeum variegatum (L.) Rumph. ex A. Juss.) is a plant in Indonesia with putative antioxidant properties. Purpose: To ascertain the composition of secondary metabolite chemicals and the antioxidant activity present in croton leaf extract (Codiaeum variegatum (L.) Rumph. ex A. Juss.) using 96% ethanol, ethyl acetate, and n-hexane solvents. Methods: The antioxidant activity was assessed using the DPPH (2,2-diphenyl-1-picrylhydrazyl) technique and quantified via UV-Vis spectrophotometry at a peak wavelength of 516.5 nm. Results: The ethyl acetate extract of croton leaves exhibited the highest antioxidant activity, with an IC50 of 11.31 ppm, whereas the IC50 values ​​for the 96% ethanol and n-hexane extracts were 13.55 ppm and 13.16 ppm, respectively. Conclusion: This study's results indicate that croton leaf extract, derived with ethyl acetate as the solvent, displays significant in vitro antioxidant activity as proven by the DPPH assay, with IC₅₀ values ​​close to those of the positive control, vitamin C, highlighting its remarkable free radical scavenging capability relative to extracts obtained with 96% ethanol and n-hexane.